Monetary policy in resource-rich economies - Ferrero, A; Seneca, M (University of Oxford, 2015)
How should monetary policy respond to a commodity price shock in a resource-rich economy? As in the baseline New Keynesian model, the central bank of a small oil-exporting economy faces a tradeo between the stabilization of domestic ination and an appropriately defined output gap. But in our framework the output gap depends on oil technology, and the weight on output gap stabilization is increasing in the importance of the oil sector. Given substantial spillovers to the rest of the economy, optimal policy calls for a reduction of the interest rate following a drop in the oil price. In contrast, a central bank with a mandate to stabilize consumer price inflation would raise interest rates to limit the inationary impact of an exchange rate depreciation.